CHEMICAL CONTROL STRATEGIES OF Commelina benghalensis IN COFFEE CROP - Da Silva, Paulo Vinicius; Barbosa, Gustavo César; Ferrari, Andréa; Tronquini, Sergio Mateus; Monquero, Patrícia Andrea (Coffee Science - ISSN 1984-3909, 2019)
The present study aims to evaluate the control of C. benghalensis by herbicides applied in post-emergence and in pre-emergence sequentially in the infesting weed in the coffee crop. Two field experiments were carried out in a coffee crop, with natural infestation of C. benghalensis, the experimental design of both was completely randomized with 4 replicates. The first experiment, involving a single application of herbicides in post-emergence presented the following treatments: (1) saflufenacil (70 g i.a. ha-1); (2) glufosinate (400 g i.a. ha-1); (3) carfentrazone (20 g i.a. ha-1); (4) flumioxazin (120 g i.a. ha-1); (5) metsulfuron (6 g i.a. ha-1), and (6) witness (without application of herbicide). In the second experiment, the treatments were: (1) saflufenacil (70 g i.a. ha-1); (2) carfentrazone (20 g i.a. ha-1); (3) flumioxazin (120 g i.a. ha-1); (4) metsulfuron (6 g i.a. ha-1), all these treatments with a sequence of indaziflam (75 g i.a. ha-1), at 21 days after the application of the treatments (DAT) of pos-emerging; (5) Witness (without application of herbicides). In the first experiment the herbicides safluenacil and flumioxazin presented the best percentages of control in post-emergence with 90 and 85.25% respectively, at 7 DAT, keeping the control superior to 80% at 21 DAT. In the second experiment, the treatments saflufenacil and flumioxazin with indaziflam sequential, presented control of 80% and 82.5% respectively at 28DAA (Days After Application). The herbicides saflufenacil and fluxioxazin represent an option for the control of C. benghalensis in post-emergence and favor the performance of the sequentially applied indaziflam herbicide.